Cyber-Victimization of People With Chronic Conditions and Disabilities: A Systematic Review of Scope and Impact. (July 2019) - Alhaboby, Zhraa A.; Barnes, James; Evans, Hala; Short, Emma
The victimization of individuals with chronic conditions or disabilities is prevalent with severe impact at psychological and physiological levels. With the increasing use of technology these experiences were further reshaped. This systematic review aimed at scoping the experiences of cyber-victimization of people living with chronic conditions or disabilities and examine the documented impact on them. Following a four-stage search strategy in several databases including MEDLINE, Embase, PsychINFO, CINAHL, Cochrane and snowballing of references, a total of 2, 922 studies were scanned and 10 studies were eventually included. Quality assessment was done in two phases using tools specific to observational studies and cyber-victimization research. A narrative synthesis of reported results covered a total of 3, 070 people. Sample size ranged between 42 and 823 participants, and the age range was 6-71 years with a majority of White ethnic backgrounds. Most studies (n=9) were cross sectional. The prevalence range of cyber-victimization was 2%-41.7% based on variable definitions, duration and methods. Targeted conditions included physical impairments, intellectual disabilities and specific chronic diseases. The most common documented impact was psychological/psychiatric, mainly depression followed by anxiety and distress. Somatic health complaints and self-harm were also reported. We concluded that people with chronic conditions and disabilities were consistently at higher risk of victimization with devastating health complications. Research gaps were identified such as the need to address more conditions and acknowledge differences between heterogeneous health conditions. Other recommendations include allowing flexibility and accountability to patients/victims in research design, education on victimization and health consequences, and improving primary care.